THE PROCESS OF ARTISTIC CREATION IN ANCIENT PERU - Choque Porras, Alba (2014)
This article provides an overview of the creating process of art in Ancient Peru. Throughout the development of Peruvian culture is undeniable presence of a minority specialization dedicated to artistic work, which should be at an intermediate level in the social structure. Due to the volume and quality of production, there were leaders artists and artists who copy, of total dedication to these tasks, because their deeds were intended for local consumption and for exchange. The art work in Ancient Peru was not meant to be an object of contemplation, these creations come to be works of cult plastic, art committed to ideological thinking, which process would have passed a series of steps to solve formal and symbolic representation.